CONSTRAINTS PERCEIVED BY THE CONTRACT FARMERS AND INTEGRATING FIRM UNDER CONTRACT DAIRY FARMING - D.V.Kolekar; H.R.Meena; Y.C.Bangar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was carried out purposively in Satara district of  Maharashtra to ascertain constraints perceived by contract dairy farmers and integrating firm under contract dairy farming system. A detailed  interview schedule in relation to various aspects of production and marketing  constraints involved in dairy farming were enlisted by asking non respondent  sample from study area through open ended questions during pilot study  and the contract dairy farmers and functionaries of integrating firm in the  study area were asked to rank the each constraint which was analyzed using  Garret’s ranking technique. Study revealed that under contract dairy farming major constraints perceived by contract dairy farmers were difficulty in  meeting quality requirements, followed by pressure for maintaining quality  of milk, delayed payment of milk produce, faulty grading of milk, delay in  arranging inputs and lack of credit for milk production. Similarly  major  constraints perceived by integrating firm were frequent milk price fluctuation  in market, followed by input diversion by farmers, farmer’s negligence in  maintaining quality, difficulty in maintaining communication with farmers, difficulty in arranging quality inputs and violation of terms and conditions by farmers.